A disaccharide crystal

By preparing LNB crystal forms with characteristic X-ray diffraction pattern peaks, and using acetone or ethanol aqueous solution to cool down and crystallization methods, the problems of LNB solid stability and low production efficiency are solved, and high-efficiency and low-cost LNB crystal forms are achieved, suitable for the preparation of LNB crystal forms. Industrialized production.

CN116462720BActive Publication Date: 2024-12-13HENRUI (QINGDAO) BIOTECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310457681.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-22
Publication Date
2024-12-13
Estimated Expiration
2043-04-22

AI Technical Summary

Technical Problem

In the prior art, the solid form of human milk oligosaccharide LNB has a problem of stability, especially in which it is prone to absorb and agglomerate during storage, and the equipment of spray drying and freeze-drying methods is large, energy consumption is high, and production efficiency is low, resulting in Increased cost and difficulty.

Method used

By preparing LNB crystal forms A and Crystal B with characteristic X-ray diffraction pattern peaks, a stable LNB crystal form is obtained by cooling and crystallization in acetone or ethanol aqueous solution containing LNB. The specific steps include preparing a solution containing LNB. , cool down and acetone or ethanol is added at a suitable temperature and speed, and high purity LNB crystals are obtained by stirring and streaming.

Benefits of technology

The stability of the LNB crystal form is achieved, the stability problem of amorphous powders during storage is overcome, and it is suitable for industrial production, reducing production costs and energy consumption, and improving production efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004199749850000011
    Figure BDA0004199749850000011
  • Figure BDA0004199749850000051
    Figure BDA0004199749850000051
  • Figure BDA0004199749850000061
    Figure BDA0004199749850000061
Patent Text Reader

Abstract

The present invention relates to a disaccharide crystal, and in particular to a new HMO crystal form. The present invention belongs to the technical field of separation and purification of enzyme catalytic reaction liquid or microbial fermentation liquid. The technical scheme of the present invention is: an LNB crystal form A, whose powder X-ray diffraction spectrum has characteristic peaks at diffraction angles (2θ±0.2°) of 6.28, 9.59, 10.30 and 19.33. The present invention also provides an LNB crystal form B, whose powder X-ray diffraction spectrum has characteristic peaks at diffraction angles (2θ±0.2°) of 6.25, 9.58 and 19.31. The LNB crystal form of the present invention has stable properties and solves the stability problem of amorphous powder during storage. The preparation method of the LNB crystal form is simple to operate and suitable for industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a crystal form of human milk oligosaccharide, and belongs to the technical field of separation and purification of enzyme catalytic reaction liquid or microbial fermentation liquid. Background Art

[0002] Breast milk is a complex mixture of carbohydrates, fats, proteins, vitamins and trace elements, and is the gold standard for infant nutrition. Among them, human milk oligosaccharides (HMOs), or breast milk oligosaccharides, have been found to be the third largest solid component in breast milk after lactose and fat. There are hundreds of types of HMOs with complex structures. Human milk oligosaccharides all contain a lactose (Gal-β-1,4-Glc) at the reducing end, and on this basis, the lactose-N-disaccharide (Gal-β-1,3-N-GlcNAc, type I chain structure) or N-acetyllactose (Gal-β-1,4-N-GlcNAc, type II chain structure) is connected with β-1,3 or β-1,6 bonds to extend the sugar chain to form core structures such as lactose-N-tetraose, lactose-N-neotetraose, and lactose-N-hexaose. Based on the core structure, the sugar chain can be modified with different numbers of fucose and sialic acid to form a variety of oligosaccharide structures. HMOs have been proven to play a very important role in the healthy development of infants and young children.

[0003] Lactose-N-biose (LNB, CAS: 50787-09-2, chemical formula as formula I) is one of the important core structures of HMOs. It has been found to be a prebiotic with biological activity, which can promote the proliferation of bifidobacteria in the intestine, inhibit the colonization of pathogens, and has a positive effect on preventing infectious diarrhea in infants and young children and enhancing the immunity of infants and young children; on the other hand, it also has a beneficial effect on the brain cognitive development of infants and young children. At present, LNB is generally prepared by chemical or biological methods, and the obtained reaction solution can be separated and purified, and then filtered and dried by evaporation concentration, freezing technology or spray drying to obtain its solid form.

[0004]

[0005] Spray drying is a common method, but the raw materials are easy to stick to the inner wall of the equipment during the spraying process, there is material loss during the spraying process, the physical and chemical properties of some raw materials are changed due to high temperature, and the amorphous powder obtained has strong hygroscopicity, which increases the difficulty of product storage and use. CN110483652A records the technology of obtaining human milk oligosaccharides (HMOs) in amorphous solid form by freeze drying, but the obtained freeze-dried powder also needs to be frozen and / or low temperature during its storage and transportation, which increases the cost and difficulty of product storage and use; and the freeze-drying process has the defects of large equipment investment, huge energy consumption in the freeze-drying process, and low production efficiency.

[0006] Stability experiments have shown that LNB in ​​amorphous solid form has stability problems such as content decrease and moisture absorption and agglomeration during storage.

[0007] Chinese patent CN113331429A records that lactose-N-disaccharide (LNB) has poor thermal stability, and solves the thermal stability problem by embedding lactose-N-disaccharide in protein / polysaccharide nanoparticles.

[0008] In summary, there is an urgent need to develop a stable LNB solid to solve the stability problem during storage. Summary of the invention

[0009] Purpose of the invention: To provide a stable LNB crystal form and a preparation method thereof, to achieve the iteration of LNB separation and purification technology and solid product form, and to provide a low-cost, efficient and reliable technology for industrial large-scale production.

[0010] The technical solution of the present invention is:

[0011] Specifically, in a first aspect of the present invention, there is provided an LNB crystal form A, whose powder X-ray diffraction pattern has characteristic peaks at diffraction angles (2θ±0.2°) of 6.28, 9.59, 10.30 and 19.33.

[0012] Preferably, the LNB crystal form A has a powder X-ray diffraction spectrum having characteristic peaks at diffraction angles (2θ±0.2°) of 6.28, 8.23, 9.59, 10.30, 16.24, 19.33, 20.55, 21.20, 21.54 and 22.52.

[0013] Preferably, the LNB form A has a powder X-ray diffraction spectrum having characteristic peaks at diffraction angles (2θ±0.2°) of 6.28, 8.23, 9.59, 10.30, 16.24, 19.33, 20.55, 21.20, 21.54, 22.52, 25.08, 26.52, 28.85, 39.51 and 39.50.

[0014] In a second aspect of the present invention, the present invention provides an LNB crystal form B, whose powder X-ray diffraction spectrum has characteristic peaks at diffraction angles (2θ±0.2°) of 6.25, 9.58, and 19.31.

[0015] Preferably, the LNB crystal form B has a powder X-ray diffraction spectrum with characteristic peaks at diffraction angles (2θ±0.2°) of 6.25, 9.58, 19.31, 20.55 and 23.40.

[0016] Preferably, the LNB form B has a powder X-ray diffraction spectrum having characteristic peaks at diffraction angles (2θ±0.2°) of 6.25, 9.58, 16.25, 19.31, 19.77, 20.55, 21.36, 22.59, 23.40, 23.80 and 26.52.

[0017] The above-mentioned X-ray diffraction analysis was carried out according to the X-ray diffraction method (second method powder X-ray diffraction method) specified in Part IV 0451 of the "Chinese Pharmacopoeia" (2020 edition).

[0018] The LNB crystal form A and the crystal form B of the present invention have the same melting point range, which is 184-186°C.

[0019] The third aspect of the present invention provides a method for preparing a LNB crystal form.

[0020] Preferably, the method for preparing the LNB crystal form A is to separate LNB solid from an acetone aqueous solution containing LNB.

[0021] Preferably, the method for preparing the LNB crystal form B is to separate LNB solid from an ethanol aqueous solution containing LNB.

[0022] The method for preparing LNB crystal form A or crystal form B of the present invention specifically comprises the following steps:

[0023] Step 1. Prepare a solution containing LNB for later use. Preferably, the concentration of the LNB solution is 0.2-0.6 g / mL;

[0024] Step 2. Cooling the LNB solution obtained in step 1 for later use;

[0025] Preferably, the temperature is lowered to 25°C or lower than 25°C. More preferably, when preparing Form A, the cooling rate is preferably 0.8-2.0°C / min, and should not be too fast; and set aside. A cooling rate higher than 2.0°C / min will affect the purity of the crystalline form.

[0026] When preparing Form B, the cooling rate should be 0.4-0.6°C / min, not too fast; a cooling rate higher than 0.6°C / min, or lower than 0.4°C / min, will affect the purity of the crystalline form.

[0027] Step 3. Under stirring, add acetone to the solution in step 2 to obtain Form A.

[0028] Under stirring, anhydrous ethanol or ethanol aqueous solution is added to the solution in step 2 to obtain Form B; or, under stirring, ethanol is added to the solution in step 2 to obtain Form B.

[0029] Preferably, the amount of acetone added is equal to or greater than the volume of water. Preferably, the volume ratio of water to acetone is 1:2-4.5; more preferably 1:2.5-4, and further preferably 1:3. When the volume of acetone used is less than 2 times the volume of water (volume), the purity of the LNB crystal form A product will be affected; when the amount of acetone used is more than 4.5 times the volume of water, the yield of LNB crystal form A will be affected.

[0030] Preferably, acetone is added under stirring at a flow rate of 0.6-1.9 mL / min; after the addition is completed, crystals are grown under stirring;

[0031] Preferably, the acetone is added in the following manner: acetone is added under stirring at a flow rate of 0.9-1.5 mL / min; after the addition is completed, crystals are grown under stirring; a flow rate lower than 0.6 mL / min affects production efficiency; a flow rate higher than 1.9 mL / min affects the formation of the crystalline form, and even the crystal form A described in the present invention cannot be obtained.

[0032] Preferably, the amount of anhydrous ethanol or ethanol aqueous solution added is equal to or greater than the volume of water. Preferably, the volume ratio of water to ethanol (in terms of anhydrous ethanol) is 1:2-5; more preferably 1:3-4, and further preferably 1:3.2-3.6. When the volume of ethanol used is less than 2 times the volume of water (volume), the purity of the LNB crystal form B product will be affected; when the amount of ethanol used is more than 5 times the volume of water, the yield of the LNB crystal form B will be affected.

[0033] Preferably, the anhydrous ethanol or ethanol aqueous solution is added in the following manner: ethanol or ethanol aqueous solution is added under stirring at a flow rate of 1.2-2.5 mL / min; after the addition is completed, crystals are grown under stirring; a flow rate lower than 1.2 mL / min affects production efficiency; a flow rate higher than 2.5 mL / min affects the formation of Form B, and Form B described in the present invention may even fail to be obtained.

[0034] In this step, seed crystals can also be added, and the seed crystals are crystal form A or crystal form B;

[0035] Preferably, the stirring rate during the crystallization process is above 100 r / min.

[0036] Preferably, after the addition of acetone or ethanol is completed, stirring is continued, and the crystal growing time is preferably not less than 12 hours.

[0037] Preferably, the LNB crystal form A or crystal form B of the present invention can be obtained by adding acetone or ethanol to the fermentation liquid containing LNB purified by decolorization, desalination, etc., and then cooling and crystallizing; or it can be obtained by adding acetone or ethanol to the aqueous solution prepared by LNB solid, and then cooling and crystallizing. The cooling crystallization refers to cooling to a temperature below 25°C.

[0038] The lactose-N-disaccharide (LNB) crystal form A or crystal form B of the present invention can be used as an intermediate for synthesizing other sugars or compounds, and can also be used as a nutritional supplement for dairy products or foods.

[0039] The source of LNB in ​​the present invention can be a reaction solution prepared according to the prior art, which is purified and prepared into a solid form, such as obtaining LNB solid by spray drying or freeze drying technology.

[0040] Beneficial Effects

[0041] The present invention provides LNB crystal form A and crystal form B, and provides a preparation method thereof. The LNB crystal form A and crystal form B are stable in nature, and overcome the stability problem of amorphous powder during storage. The preparation method of the LNB crystal form A and crystal form B is simple to operate and suitable for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1 .X-ray powder diffraction pattern of LNB form A.

[0043] Figure 2 .X-ray powder diffraction pattern of LNB form B.

[0044] Figure 3 .The morphology of LNB amorphous powder and Form A before stability test (the left side is LNB amorphous powder, and the right side is LNB Form A of the present invention).

[0045] Figure 4 .The morphology of LNB amorphous powder and Form A after stability test (the left side is LNB amorphous powder, and the right side is LNB Form A of the present invention).

[0046] Figure 5 .The morphology of LNB amorphous powder and crystal form B before stability test (the left side is LNB crystal form B, the right side is LNB amorphous powder)

[0047] Figure 6.Morphology of LNB amorphous powder and Form B after stability test (LNB Form B on the left, LNB amorphous powder on the right). DETAILED DESCRIPTION

[0048] It should be noted that the following description and examples are exemplary and are intended to provide further explanation of the present application. Unless otherwise specified, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which the present application belongs.

[0049] The present invention is further explained by the following examples, but they are not intended to limit the present invention. It should be understood that these examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention. The test methods in the following examples without specifying specific conditions are usually carried out under normal conditions.

[0050] The LNB content of the product of the embodiment was determined by HPLC. The detection conditions were: chromatographic column model: Aminex HPX-87H (300×7.8 mm), mobile phase: 5 mM H2SO4 aqueous solution, column temperature 30° C., injection volume 10 μL, UV detector (Hitachi Chromaster), wavelength 210 nm, flow rate 0.5 mL / min.

[0051] The crystal form obtained in the example was subjected to X-ray diffraction (XRD) detection according to the X-ray diffraction method (second method powder X-ray diffraction method) specified in Appendix 0451 of the Chinese Pharmacopoeia (2020 edition).

[0052] According to the method specified in GB / T21781-2008 "Test method for melting point and melting range of chemicals - capillary method", the melting point of the solid or crystal obtained in the example was tested.

[0053] Example 1. Preparation of LNB reaction solution and acquisition of amorphous powder

[0054] Reference is made to the method described in Example 3 of Chinese patent application number 201911055516.5, entitled “A method for synthesizing lacto-N-biose”.

[0055] "Add 10mM galactose, 5mM ATP, 5mM acetyl phosphate, 10mM GlcNAc, 3mM MgCl2, 100mM Tris-HCl, 5U Galk, 3U ACK, and 168U LNBP to 1mL of the reaction system. After reacting at 37℃ for 12h, the reaction system was boiled for 5min, centrifuged, and the supernatant was collected. After filtering with a membrane, the supernatant was passed through a Biorad-HPX column to obtain a reaction solution containing LNB."

[0056] The above reaction system was enlarged to 10 L to obtain a reaction solution containing LNB. Half of the reaction solution was rapidly spray-dried at 50° C. to obtain a solid powder, which was an amorphous solid powder. The purity was 94.72% as measured by HPLC, and the melting point was 165.2° C.

[0057] Example 2. Crystallization study of LNB Form A

[0058] Step 1. Take 8 g of the LNB solid powder obtained in Example 1, add 20 mL of purified water, and gently stir at 50-60° C. until it is completely dissolved.

[0059] Step 2. Filter the solution obtained in step 1, cool the filtrate to 25°C under stirring at a cooling rate of 1.4°C / min, add 60 mL of acetone at a flow rate of 1.3 mL / min, and grow the crystals for 48 hours under stirring.

[0060] Step 3. Filter by suction, wash with 0-8°C precooled acetone, and vacuum freeze-dry under vacuum degree 1Pa and temperature -20°C to obtain LNB crystals. The purity of LNB crystals was determined by HPLC, and the purity of LNB crystals was 98.56% calculated by standard curve. The yield was 83%, the melting point was 185.5°C, and the X-ray powder diffraction pattern was shown in Figure 1 The diffraction peaks and related characteristic data are shown in Table 1, and the crystal form is called crystal form A.

[0061] Table 1

[0062]

[0063]

[0064] Example 3. Crystallization study of LNB Form A

[0065] Step 1. Take 5 g of the LNB solid powder obtained in Example 1, add 25 mL of purified water, and gently stir at 50-60° C. until it is completely dissolved.

[0066] Step 2. Filter the solution obtained in step 1, cool the filtrate to 20°C under stirring at a cooling rate of 2.0°C / min, add 50 mL of acetone at a flow rate of 0.6 mL / min, and grow the crystals for 48 hours under stirring.

[0067] Step 3: Filter by suction, wash with acetone precooled at 0-8°C, and freeze-dry under vacuum at a vacuum degree of 1 Pa and a temperature of -20°C to obtain LNB crystals.

[0068] The purity of LNB crystals was determined by HPLC and calculated by standard curve to be 98.12%. The yield was 80.6%. Its X-ray powder diffraction pattern was the same as that of the crystal form A obtained in Example 2. The melting point was 184.3°C.

[0069] Example 4. Crystallization study of LNB Form A.

[0070] Step 1. Take 15 g of the LNB solid powder obtained in Example 1, add 25 mL of purified water, and gently stir at 50-60° C. until it is completely dissolved.

[0071] Step 2. Filter the solution obtained in step 1, cool the filtrate to 20°C under stirring at a cooling rate of 0.8°C / min, add 112.5 mL of acetone at a flow rate of 1.9 mL / min, and grow the crystals for 40 hours under stirring.

[0072] Step 3: Filter by suction, wash with acetone precooled at 0-8°C, and freeze-dry under vacuum at a vacuum degree of 1 Pa and a temperature of -20°C to obtain LNB crystals.

[0073] The purity of LNB crystals was determined by HPLC and calculated by standard curve to be 98.87%, with a yield of 78.6%. Its X-ray powder diffraction pattern was the same as that of the crystal form A obtained in Example 2, with a melting point of 185.6°C.

[0074] Example 5. Crystallization study of LNB Form A.

[0075] The purified reaction solution containing LNB obtained in Example 1 was treated as follows.

[0076] Step 1. The purified reaction solution containing LNB is concentrated by rotary evaporation at 50° C. to obtain LNB concentrated solution (LNB concentration is 400-600 g / L).

[0077] Step 2. Take 10 mL of the concentrated solution obtained in step 1, filter, and cool the filtrate to 25°C while stirring at a cooling rate of 1.5°C / min. Add 0.06 g of seed crystals to seed the crystals, add 30 mL of acetone, and stir at a flow rate of 1.5 mL / min for 48 hours.

[0078] Step 3: Filter by suction, wash with acetone precooled at 0-8°C, and freeze-dry under vacuum at a vacuum degree of 1 Pa and a temperature of -20°C to obtain LNB crystals.

[0079] The purity of LNB crystals was determined by HPLC and calculated by calibration curve to be 99.06%, with a yield of 81.4% and a melting point of 185.8°C. Its X-ray powder diffraction pattern was the same as that of the crystal form A obtained in Example 2.

[0080] Comparative Example 1. Study on the effect of cooling rate and acetone flow acceleration on the crystallization of LNB.

[0081] Step 1. Take 5 g of the LNB solid powder obtained in Example 1, add 25 mL of purified water, and gently stir at 50-60° C. until it is completely dissolved.

[0082] Step 2. Filter the solution obtained in step 1, cool the filtrate to 10°C under stirring at a cooling rate of 2.5°C / min, add 50 mL of acetone at a flow rate of 2.5 mL / min, and grow the crystals for 40 hours under stirring.

[0083] Step 3: Filter by suction, wash with acetone precooled at 0-8°C, and freeze-dry under vacuum at a vacuum degree of 1 Pa and a temperature of -20°C to obtain LNB crystals.

[0084] The purity of LNB crystals was determined by HPLC and calculated by standard curve to be 93.36%, with a yield of 75.5% and a melting point of 170.4°C.

[0085] Comparative Example 2. Study on the effects of cooling rate, acetone dosage and flow acceleration on the crystallization of LNB.

[0086] Step 1. Take 5 g of the LNB solid powder obtained in Example 1, add 25 mL of purified water, and gently stir at 50-60° C. until it is completely dissolved.

[0087] Step 2. Filter the solution obtained in step 1, cool the filtrate to 10°C under stirring at a cooling rate of 0.4°C / min, add 130 mL of acetone at a flow rate of 3.0 mL / min, and grow the crystals for 40 hours under stirring.

[0088] Step 3: Filter by suction, wash with acetone precooled at 0-8°C, and freeze-dry under vacuum at a vacuum degree of 1 Pa and a temperature of -20°C to obtain LNB crystals.

[0089] The purity of LNB crystals was determined by HPLC and calculated by standard curve to be 95.82%, with a yield of 62.5% and a melting point of 173.4°C.

[0090] Example 6. Crystallization study of LNB Form B.

[0091] Step 1. Take 8 g of the LNB solid powder obtained in Example 1, add 20 mL of purified water, and gently stir at 50-60° C. until it is completely dissolved.

[0092] Step 2. Filter the solution obtained in step 1, cool the filtrate to 25°C under stirring at a cooling rate of 0.5°C / min, add 68 mL of anhydrous ethanol at a flow rate of 1.8 mL / min, and grow the crystals for 40 hours under stirring.

[0093] Step 3: Filter by suction, wash with anhydrous ethanol precooled at 0-8°C, and vacuum freeze-dry at a vacuum degree of 1 Pa and a temperature of -20°C to obtain LNB crystals.

[0094] The purity of LNB crystals was then determined by HPLC. The purity of LNB crystals was 98.56% by standard curve calculation, the melting point was 185.9°C, the yield was 81%, and the X-ray powder diffraction pattern was shown in Figure 2 The diffraction peaks and related characteristic data are shown in Table 2, and the crystal form is called crystal form B.

[0095] Table 2

[0096]

[0097]

[0098]

[0099] Example 7. Crystallization study of LNB Form B.

[0100] Step 1. Take 5 g of the LNB solid powder obtained in Example 1, add 25 mL of purified water, and gently stir at 50-60° C. until it is completely dissolved.

[0101] Step 2. Filter the solution obtained in step 1, cool the filtrate to 20°C under stirring at a cooling rate of 0.4°C / min, add 50 mL of anhydrous ethanol at a flow rate of 1.2 mL / min, and grow the crystals for 48 hours under stirring.

[0102] Step 3: Filter by suction, wash with anhydrous ethanol precooled at 0-8°C, and vacuum freeze-dry at a vacuum degree of 1 Pa and a temperature of -20°C to obtain LNB crystals.

[0103] Then, the purity of the LNB crystals was determined by HPLC. The purity of the LNB crystals obtained by calibration curve calculation was 98.16%, the yield was 80.6%, the melting point was 184.2° C., and its X-ray powder diffraction pattern was the same as that of the crystal form B obtained in Example 6.

[0104] Example 8. Crystallization study of LNB Form B.

[0105] Step 1. Take 15 g of the LNB solid powder obtained in Example 1, add 25 mL of purified water, and gently stir at 50-60° C. until it is completely dissolved.

[0106] Step 2. Filter the solution obtained in step 1, cool the filtrate to 20°C under stirring at a cooling rate of 0.6°C / min, add 125 mL of anhydrous ethanol at a flow rate of 2.5 mL / min, and grow the crystals for 40 hours under stirring.

[0107] Step 3: Filter by suction, wash with anhydrous ethanol precooled at 0-8°C, and vacuum freeze-dry at a vacuum degree of 1 Pa and a temperature of -20°C to obtain LNB crystals.

[0108] The purity of the LNB crystals was then determined by HPLC. The purity of the LNB crystals obtained by calibration curve calculation was 98.5%, and the yield was 78.5%. Its X-ray powder diffraction pattern was the same as that of the crystal form B obtained in Example 6, and the melting point was 185.6°C.

[0109] Example 9. Crystallization study of LNB Form B.

[0110] The reaction solution containing LNB obtained in Example 1 was treated as follows.

[0111] Step 1. The LNB purified solution was concentrated by rotary evaporation at 50°C to obtain LNB concentrated solution (LNB concentration was 400-600 g / L).

[0112] Step 2. Take 10 mL of the concentrated solution obtained in step 1, filter it, and cool the filtrate to 25°C while stirring at a cooling rate of 0.5°C / min. Add 0.06 g of seed crystals to seed the crystals, add 35 mL of anhydrous ethanol, stir at a flow rate of 1.8 mL / min, and grow the crystals for 48 hours.

[0113] Step 3: Filter by suction, wash with anhydrous ethanol precooled at 0-8°C, and vacuum freeze-dry at a vacuum degree of 1 Pa and a temperature of -20°C to obtain LNB crystals.

[0114] The purity of the LNB crystals was then determined by HPLC. The purity of the LNB crystals obtained by calibration curve calculation was 99.02%, with a yield of 78%. Its X-ray powder diffraction pattern was the same as that of the crystal form B obtained in Example 6, with a melting point of 185.7°C.

[0115] Comparative Example 3. Study on the effects of cooling rate, ethanol addition amount and flow acceleration on the crystallization of LNB.

[0116] Step 1. Take 15 g of the LNB solid powder obtained in Example 1, add 25 mL of purified water, and gently stir at 50-60° C. until it is completely dissolved.

[0117] Step 2. Filter the solution obtained in step 1, cool the filtrate to 10°C under stirring at a cooling rate of 0.8°C / min, add 40 mL of anhydrous ethanol at a flow rate of 3.5 mL / min, and grow the crystals for 40 hours under stirring.

[0118] Step 3: Filter by suction, wash with anhydrous ethanol precooled at 0-8°C, and freeze-dry under vacuum at a vacuum degree of 1 Pa and a temperature of -20°C to obtain LNB solid.

[0119] Then the purity of LNB crystals was determined by HPLC. The purity of LNB crystals calculated by standard curve was 94.32%, the yield was 78.5%, and the melting point was 175.4°C.

[0120] Comparative Example 4. Study on the effects of cooling rate, ethanol addition amount and flow acceleration on the crystallization of LNB.

[0121] Step 1. Take 10 g of the LNB solid powder obtained in Example 1, add 25 mL of purified water, and gently stir at 50-60° C. until it is completely dissolved.

[0122] Step 2. Filter the solution obtained in step 1, cool the filtrate to 10°C under stirring at a cooling rate of 0.2°C / min, add 150 mL of anhydrous ethanol at a flow rate of 3.5 mL / min, and grow the crystals for 40 hours under stirring.

[0123] Step 3: Filter by suction, wash with anhydrous ethanol precooled at 0-8°C, and vacuum freeze-dry at a vacuum degree of 1 Pa and a temperature of -20°C to obtain LNB crystals.

[0124] The purity of the LNB crystals was then determined by HPLC. The purity of the LNB crystals calculated by standard curve was 94.54%, the yield was 58.5%, and the melting point was 170.8°C.

[0125] Example 10. Stability study

[0126] Weigh 5 g (accurate to 0.0001 g) of the spray-dried LNB solid powder obtained in Example 1 and the LNB crystals obtained in Examples 2-9, respectively, and put them in polyethylene plastic bags, which are sealed. Place them in a constant temperature and humidity chamber at a temperature of 40°C ± 2°C and a relative humidity of 75% ± 5% for 7 days, take them out and weigh them, calculate the weight gain, and detect the LNB content and melting point; observe the changes in appearance. The results are recorded in Tables 3-6.

[0127] Table 3. Quality study of samples on day 0 in stability experiment of Form A

[0128]

[0129]

[0130] Table 4. Quality study of samples from the 7th day of the stability experiment of Form A

[0131]

[0132] Table 5. Quality study of the 0-day sample of Form B stability experiment

[0133] sample LNB, % Melting point, °C Appearance Example 1 Amorphous Powder 94.72 165.2 Off-white uniform powder Example 6 Crystal Form B 98.56 185.9 Off-white uniform crystal Example 7 Crystal Form B 98.16 184.2 Off-white uniform crystal Example 8 Crystal Form B 98.54 185.6 Off-white uniform crystal Example 9 Crystalline Form B 99.02 185.7 Off-white uniform crystal

[0134] Table 6. Quality study of samples from the 7th day of the stability experiment of Form B

[0135]

[0136]

[0137] Stability test description:

[0138] The amorphous powder obtained by the spraying method in Example 1 becomes darker in color after the stability test (see attached) Figure 3-6 ), there are larger agglomerated particles, and the LNB content is reduced. After the stability test, the color and content of the crystal form A and the crystal form B obtained by the present invention have no obvious changes.

[0139] As described above, the LNB crystal forms A and B obtained in the present invention have ideal stability, are conducive to the storage of the product, and solve the stability problem of amorphous LNB.

[0140] It should be noted that the above examples are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention is described in detail with reference to the given examples, those skilled in the art may modify or replace the technical solution of the present invention as needed without departing from the spirit and scope of the technical solution of the present invention.

Claims

1. An LNB crystal form A, characterized in that: Its powder X-ray diffraction spectrum has characteristic peaks at diffraction angles (2θ±0.2°) of 6.28, 8.23, 9.59, 10.30, 16.24, 19.33, 20.55, 21.20, 21.54 and 22.52, and its melting point is 184-186°C.

2. The LNB crystal form A according to claim 1, characterized in that: Its powder X-ray diffraction spectrum has characteristic peaks at diffraction angles (2θ±0.2°) of 6.28, 8.23, 9.59, 10.30, 16.24, 19.33, 20.55, 21.20, 21.54, 22.52, 25.08, 26.52, 28.85, 39.51 and 39.

50.

3. An LNB crystal form B, characterized in that: Its powder X-ray diffraction spectrum has characteristic peaks at diffraction angles (2θ±0.2°) of 6.25, 9.58, 16.25, 19.31, 20.55, 21.36, 22.59 and 23.40, and its melting point is in the range of 184-186°C.

4. The LNB crystal form B according to claim 3, characterized in that: Its powder X-ray diffraction spectrum has characteristic peaks at diffraction angles (2θ±0.2°) of 6.25, 9.58, 16.25, 19.31, 19.77, 20.55, 21.36, 22.59, 23.40, 23.80 and 26.

52.

5. The method for preparing LNB crystal form A according to any one of claims 1 to 2, characterized in that: The steps include: Step 1. Prepare LNB aqueous solution with a concentration of 0.2-0.6 g / mL for later use; Step 2. Cool the LNB solution obtained in step 1 to 25°C or below, at a cooling rate of 0.8-2.0°C / min, and set aside; Step 3. Under stirring, add acetone to the solution in step 2, and control the amount of acetone added so that the volume ratio of water to acetone is in the range of 1:2-4.5, and the flow rate of acetone is 0.6-1.9 mL / min; Step 4: Separate, wash and dry to obtain Form A.

6. The method for preparing LNB crystal form A according to claim 5, characterized in that: In step 3, the amount of acetone added is controlled so that the volume ratio of water to acetone is in the range of 1:2.5-4, and the acetone flow rate is 0.9-1.5 mL / min.

7. The method for preparing LNB crystal form A according to claim 5, characterized in that: In step 3, the amount of acetone added is controlled so that the volume ratio of water to acetone is 1:3, and the acetone flow rate is 0.9-1.5 mL / min.

8. The method for preparing LNB crystal form B according to any one of claims 3 to 4, characterized in that: The steps include: Step 1. Prepare LNB aqueous solution with a concentration of 0.2-0.6 g / mL for later use; Step 2. Cool the LNB solution obtained in step 1 to 25°C or below, at a cooling rate of 0.4-0.6°C / min, and set aside; Step 3. Under stirring, add ethanol to the solution in step 2, and control the amount of ethanol added so that the volume ratio of water to ethanol is in the range of 1:2-5, and the flow rate of ethanol is 1.2-2.5 mL / min; Step 4: Separate, wash and dry to obtain Form B.

9. The method for preparing LNB crystal form B according to claim 8, characterized in that: In step 3, the amount of ethanol added is controlled so that the volume ratio of water to ethanol is in the range of 1:3-4.

10. The method for preparing LNB crystal form B according to claim 8, characterized in that: In step 3, the amount of ethanol added is controlled so that the volume ratio of water to ethanol is in the range of 1:3.2-3.6.